Haploinsufficiency of progranulin causes impairments in PINK/PARKIN mitophagy: Molecular and cell biology/TDP‐43. (7th December 2020) - Casey, Jackie M.; Melandri, Daniela; Arber, Charles; Soutar, Marc; Holler, Christopher J.; Kukar, Thomas; Isaacs, Adrian M.; Rohrer, Jonathan D.; Plun‐Favreau, Helene; Wray, Selina
Abstract: Background: GRN mutations, resulting in haploinsufficiency of progranulin, cause frontotemporal dementia (FTD) with TDP‐43 pathology. Impairments in mitophagy, the selective autophagy of damaged mitochondria, have been identified in several neurodegenerative diseases, and multiple neurodegenerative disease genes, including PINK1, Parkin, VCP and TBK1, have been shown to play a role in this pathway. A role for progranulin in the regulation of neuronal mitophagy has not been explored, however progranulin deficient mice exhibit reduced xenophagy (selective clearance of bacteria). We therefore hypothesised that loss of progranulin could lead to defective mitophagy. Method: We used two in vitro models to investigate PINK1/Parkin mitophagy: SHSY5Y cells overexpressing Parkin (PoE‐SHSY5Y) +/‐ siRNA against GRN, and induced pluripotent stem cell (iPSC) derived cortical neurons from two patients with FTD‐associated GRN mutations (R493X and C31fs). PINK1/Parkin mitophagy was induced using a combination of Antimycin A (respiratory complex III inhibitor) and oligomycin (ATP synthase inhibitor), and PINK1 accumulation and levels of S65 phosphorylated ubiquitin (the substrate of PINK1 and a marker of its activity) were examined using western blot and immunofluorescence. Subsequent mitophagy was assessed by examining Mitofusin‐2 ubiquitination and degradation, and TIM23 levels by western blot. Result: A reduction in progranulin levels resulted in reduced accumulation of PINK1 and lower levels of mitochondrial phospho‐ubiquitin following oligomycin/antimycin treatment in both PoE‐SHSY5Y and iPSC‐neurons with GRN mutations. Ubiquitination and degradation of mitofusin‐2 was also decreased in cells with reduced progranulin. Conclusion: These results suggest that progranulin plays a role in mitophagy by regulating stability and/or activity of PINK1. Ongoing work aims to understand the mechanisms by which progranulin and/or individual granulins contribute to this process and to dissect cell‐type specific contributions of progranulin to mitophagy in iPSC‐ derived neurons, astrocytes and microglia.